Analysis of the Influence of Geomechanical Parameters and Geometry on Slope Stability in Granitic Residual Soils - Matías F. Bravo-Zapata; Enrique Muñoz; Pablo Lapeña-Mañero; José Miguel Montenegro-Cooper; Robert W. King (Applied Sciences, 2022)
Granitic residual soils are soils formed by the in situ weathering of intrusive granitic rocks and are present in different parts of the world. Due to their large presence, many civil engineering projects are carried out on and within these soils. Therefore, a correct characterization of the slopes is necessary for slope stability studies. This investigation aims to study the influence of the values of geomechanical parameters (specific weight, cohesion, and friction angle) and the geometry of a slope (height and inclination) on slope stability of residual granitic soils in dry and static conditions. To this end, an automatic system was developed for the numerical study of cases using the finite element method with limit analysis. The system allows modeling, through Monte Carlo simulation and different slope configurations. With this system, the safety factors of 5000 cases were obtained. The results of the models were processed through the SAFE toolbox, performing a Regional Sensitivity Analysis (RSA). The results of this research concluded that the order of influence of the factors were: slope angle > slope height > cohesion > friction angle > unit weight (β > H > c > <semantics>ϕ</semantics> > γ).